2021
DOI: 10.1038/s41467-021-20893-2
|View full text |Cite
|
Sign up to set email alerts
|

CAR-T cell-mediated depletion of immunosuppressive tumor-associated macrophages promotes endogenous antitumor immunity and augments adoptive immunotherapy

Abstract: The immunosuppressive tumor microenvironment (TME) represents a major barrier for effective immunotherapy. Tumor-associated macrophages (TAMs) are highly heterogeneous and plastic cell components of the TME which can either promote tumor progression (M2-like) or boost antitumor immunity (M1-like). Here, we demonstrate that a subset of TAMs that express folate receptor β (FRβ) possess an immunosuppressive M2-like profile. In syngeneic tumor mouse models, chimeric antigen receptor (CAR)-T cell-mediated selective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
152
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 198 publications
(155 citation statements)
references
References 102 publications
2
152
0
1
Order By: Relevance
“…In this regard, therapeutic strategies against immunosuppressive populations (e.g., tumor-associated macrophages, Tregs etc. ), leukemia-supporting molecules expressed by stroma cells, altered cytokine networks and immune checkpoint signals are under investigation in several solid and hematological malignancies [ 136 , 137 ]. At this purpose, chimeric receptor antigen (CAR)-T cells, antibodies against developmental pathways (e.g., anti-CSF1R antibody) [ 111 ], neutralizing antibodies for soluble factors [ 44 ] (e.g., inflammatory cytokines, BMP4, Activin A etc.)…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, therapeutic strategies against immunosuppressive populations (e.g., tumor-associated macrophages, Tregs etc. ), leukemia-supporting molecules expressed by stroma cells, altered cytokine networks and immune checkpoint signals are under investigation in several solid and hematological malignancies [ 136 , 137 ]. At this purpose, chimeric receptor antigen (CAR)-T cells, antibodies against developmental pathways (e.g., anti-CSF1R antibody) [ 111 ], neutralizing antibodies for soluble factors [ 44 ] (e.g., inflammatory cytokines, BMP4, Activin A etc.)…”
Section: Resultsmentioning
confidence: 99%
“…Elimination of M2 polarized macrophages from the tumor microenvironment with m909 could potentially improve the efficacy of chemotherapy or immunotherapy treatments targeting the tumor cells directly when used in combination. M2 polarized TAMs are also not unique to ovarian cancer and occur in the microenvironment of many solid cancers making their application broader [ 21 , 45 ]. Unfortunately, there are also challenges in replicating the tumor microenvironment and further experiments to demonstrate the efficacy of m909 in vivo or in combination with other therapeutic agents requires transitioning away from a human NK reconstituted mouse model, as a functional immune system is necessary to represent the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Rodriguez-Garcia et al highlighted the role of folate receptor b (FRb) in TAMs cells. They demonstrated that immunosuppressive M2 TAMs expressing FRb promote tumor progression in a mouse model of ovarian cancer, pointing out FRb as a potential therapeutic target in combination with chemo-or immunotherapy (200). Furthermore, the expression of FRb in M2 TAMs correlated with a poor prognosis also in pancreatic cancer (201).…”
Section: Immune Cells Rewiring Therapiesmentioning
confidence: 99%